Structural and Semantic Peculiarities of Phraseological Units Containing the Somatic Component "Hand” - Voloshynovych, Natalia; Trotsiuk, Aida; Волошинович, Наталія; Троцюк, Аїда (Східноєвропейський національний університет імені Лесі Українки, 2014)
The article deals with the substantivized, adverbial and verbal phraseological units of modern English with the somatic component “hand”. This study has demonstrated that the somatic component “hand” is characterized by high productivity, in the sense that it is the basis of generating a great number of substantivized and verbal phraseological units. With respect to adverbial PhUs, it has been shown that they are not numerous (about 30). The most common structural type of substantivized PhUs is the structure involving attributive word-combination, for adverbial PhUs – it is a combination of one structural and one notional word and a subordinate word combination that consists of two components; for verbal PhUs the structure of subordinate word combination is the most relevant. All the PhUs which were investigated fall into one of the following three varieties in terms of phraseological meaning: idiomatisms, idiophraseomatisms, phraseomatisms. A great majority of PhUs are based on metaphor or metonymy. All of them are anthropocentric in their character. Some of them can form synonymic groups and antonymic pairs. The PhUs which were analysed can denote both people and inanimate things or both. Substantivized PhUs may express different degrees of favourability in terms of their evaluative nature: positive, negative or neutral. У статті досліджено субстантивні, адвербіальні й вербальні фразеологічні одиниці сучасної англійської мови із соматичним компонентом hand. Аналіз досліджуваних ФО дав підстави зробити такі висновки: для соматичного компонента hand характерна висока продуктивність, тобто здатність стати основою для формування великої кількості субстантивних і вербальних ФО. Щодо адвербіальних ФО, то вони нечисленні. Характерний структурний тип субстантивних ФО – атрибутивне словосполучення; для адвербіальних ФО – одновершинні ФО та двокомпонентні підрядні ФО; для дієслівних ФО структура підрядного словосполучення найбільш релевантна. Досліджувані ФО представлені трьома різновидами фразеологічного значення: ідіоматизми, ідіофразеоматизми, фразеоматизми. ФО здебільшого утворюються на основі метафоричного або метонімічного переосмислення. Усі вони характеризуються антропоцентричністю. Деякі з них можуть утворювати синонімічні групи й антонімічні пари. Крім особи, досліджувані ФО можуть позначати й неособу або і одних, і других. Субстантивні ФО характеризується позитивною, негативною або нульовою оцінкою.
Структурно-семантичні особливості фразеологічних одиниць із соматичним компонентом HAND.
Keywords: phraseological units; somatic component; idiomatism; idiophraseomatism; phraseomatism; фразеологічні одиниці; соматичний компонент; ідіоматизм; ідіофразеоматизм; фразеоматизм